PENGARUH LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA DIMEDIASI MOTIVASI KERJA PADA GURU- GURU SMK MA’ARIF COMAL PEMALANG - Samtono Samtono (Among Makarti, 2018)
AbstractThis study as to determine the effect  work  environment,  job satisfaction, on work motivation, and  its impac t on  teacher  ferformance  in  teacher’s performance  SMK  Ma’arif  Comal  Pemalang           Data were  obtained  through  a  questionare.  The  sample  used  in  the study  were  95  respondents. The  data  obtained  were  processed  using  descriptive  analysis  and  quantitative  statistical  anaylisis. Quantitative analysis  using  mutiple  regression  analysis  to  determine  the  effect  of independent  variables  on  the  dependent  variable,  bu t before  the  tes t is done  first  tested  the validity  and  reliability  testing.          Regression  analysis  showed  that  work  environment,  job  satisfaction, and  work  motivation  not  affect  the  performance  SMK  Ma’arif  Comal Pemalang. Keywords  :  Work  environment, job  satisfaction, work  motivation, performance